A time-motion analysis of the cross-over step block technique in volleyball: non-linear and asymmetric performances - Hernández-Hernández, E.; Montalvo-Espinosa, A.; Garcia-de-Alcaraz, A. (symmetry, 2020)
Blocking performance in volleyball is strongly affected by the time in which the action is executed. This study analyzes the time-motion variables in terms of the player`s role and movement direction (right or left), in different phases of the displacement and jump actions in the cross-over step block technique. A kinematic analysis was conducted with 10 senior male volleyball players. Two series of five repetitions were each recorded and classified in terms of middle-blockers (block in the center and sides of the net) and wing-players (only block in the sides). The results showed that the middle-blockers were significantly slower than the wing-players in the first (0.75 ± 0.24 vs. 0.66 ± 0.19 sec; p = 0.020; ES = -0.37 ± 0.30) and fourth phases (0.33 ± 0.8 vs. 0.29 ± 0.8 sec; p = 0.001; ES = -0.44 ± 0.31), and in the total time for blocking (3.15 ± 0.6 vs. 3 ± 0.58 sec; p = 0.003; ES = -0.23 ± 0.31). Overall, players were significantly faster when moving to the right side, showing performance asymmetries. The fastest phases were also performed just before the jump. These findings provide specific knowledge about the cross-over step block technique in its different phases and displacement direction. This information can be used to improve the movement time in the first defensive action in volleyball.